Well Logging in Nontechnical Language (2nd Edition) - Johnson, David E. (David Earl); Pile, Kathryne E. (PennWell, 2006)
An update of the PennWell classic Nontechnical Guide to Logging Techniques, this text provides an easy-to-understand overview of the technically complex subject of well logging. This book will be very useful to bankers, landmen, geology and engineering technicians, clerks, secretaries, and others who need a basic understanding of well logs to perform their jobs.